Laryngomalacia, GER, and sleep apnea are BRUEing - Sometimes! - David Gozal (Hygeia Press di Corridori Marinella, 2021)
Brief resolved unexplained events (BRUE) constitute the newest nomenclature of near-miss SIDS, later on termed ALTE. These events have been putatively assigned to the sleeping state and suspected to involve airway obstruction. The current study in the Journal (Nosetti et al., 2021, https://doi.org/10.7363/100207) identifies laryngomalacia and gastroesophageal reflux as being frequently associated with BRUE. The potential implications of such associations are discussed.